The limits to life in the terrestrial biosphere - Horvath, Jorge Ernesto (Cadernos de Astronomia, 2022)
We present in this article a broad overview of the physical limits in which living organisms can bear to develop in terms of temperature, pressure acidity and other important parameters. We also discuss the recent quantitative evaluation of biomasses of each living group and the issue of chemoautotrophic organisms.
Keywords: astrobiology; origin of life; terrestrial biosphere